Polymer alloy material, preparation method thereof and flow cell panel frame

By using polymer alloy materials with components such as polyolefins and engineering plastics in the flow cell panel frame material, a dual continuous phase structure is formed through the melt blending process, which solves the problem that existing materials are difficult to have multiple performances, and achieves low-cost and efficient production of flow cell panel frame.

CN119505413APending Publication Date: 2025-02-25BEIJING HERUI ENERGY STORAGE TECH CO LTD

Patent Information

Application Number
CN202411654058.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

It is difficult for existing flow cell panel frame materials to have high modulus, high heat resistance, strong acid resistance, low shrinkage rate and other requirements, resulting in high production costs and long processing cycle of single-piece frames, affecting the commercial promotion of flow cells.

Method used

A polymer alloy material, including polyolefins, engineering plastics, compatible modifiers, inorganic fillers and functional additives, is used to form a "sea-sea" microdispersed feature and tightly bound bicontinuous phase structure through a melt blending process.

Benefits of technology

It has achieved a variety of properties such as high flow, high modulus, high heat resistance, strong acid resistance, and low shrinkage ratio of polymer materials. It is suitable for mass production of liquid flow panel frames, reducing costs and improving production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005143599520000081
    Figure BDA0005143599520000081
Patent Text Reader

Abstract

The invention provides a polymer alloy material, a preparation method thereof and a flow cell panel frame, and belongs to the technical field of high polymer materials. The polymer alloy material comprises the following components: 25-80% of polyolefin, 10-20% of engineering plastic, 1-5% of a compatilizer, 5-50% of an inorganic filler and 0.1-5% of an auxiliary agent. Wherein the engineering plastic is selected from one or more of a styrene methyl methacrylate copolymer, a styrene-butadiene methyl methacrylate copolymer, polycarbonate, polyphenyl ether, polyphenylene sulfide, a styrene-maleic anhydride copolymer or a styrene-acrylonitrile copolymer. The polymer alloy material forms a bicontinuous phase structure with'sea-sea 'microscopic dispersion characteristic and tight interface bonding, can simultaneously have the characteristics of excellent heat resistance, corrosion resistance, high flow, low shrinkage, high modulus and the like, and makes up for the defect of insufficient performance of the existing liquid flow cell panel frame plate PP material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a polymer alloy material and a preparation method thereof, and a flow battery plate frame. Background Art

[0002] Liquid flow battery is a kind of energy storage battery system with great application prospects. Plate frame is the key structural component of iron-chromium liquid flow battery stack, which affects the operating life of iron-chromium liquid flow battery stack. As the load-bearing component in the liquid flow battery stack, the plate frame generally adopts a multi-layer plate frame stacking and sealing structure to accommodate the reaction of electrodes, diaphragms and flowing electrolytes. At present, the plate frame materials of liquid flow batteries generally use CPVC (chlorinated polyvinyl chloride), PPH (homopolymer polypropylene) and other materials, and the processing method selected is generally machining. However, it is difficult for these existing polymer materials to balance multiple requirements such as high modulus, high heat resistance, strong acid resistance, low shrinkage rate, and low cost. When it is used as the plate frame material of liquid flow battery, the plate frame of the manufactured liquid flow battery has problems such as difficulty in injection molding, easy warping, easy softening at high temperature, high cost, or poor installation quality, which leads to high plate frame machining cost, long single plate frame machining cycle, and unsuitability for mass production of plate frame, affecting the commercial promotion of liquid flow battery.

[0003] Therefore, it is necessary for the present invention to provide a polymer alloy material and a preparation method thereof to solve the problem that existing alloy materials are difficult to simultaneously have high modulus, high heat resistance, strong acid resistance, and low shrinkage rate, so as to meet the high usage requirements of liquid flow battery stacks for plate and frame materials. Summary of the invention

[0004] The main purpose of the present invention is to provide a polymer alloy material and a preparation method thereof and a liquid flow battery plate frame, so as to overcome the problem in the prior art that the liquid flow battery plate frame material is difficult to have high modulus, high heat resistance, strong acid resistance and low shrinkage rate at the same time.

[0005] In order to achieve the above-mentioned object, the present invention provides a polymer alloy material, which comprises the following components in weight percentage: 25-80% of polyolefin, 10-20% of engineering plastic, 1-5% of compatibility modifier, 5-50% of inorganic filler, and 0.1-5% of functional additive; wherein the engineering plastic is selected from one or more of styrene methyl methacrylate copolymer (MS), styrene butadiene methyl methacrylate copolymer (MBS), polycarbonate (PC), polyphenylene oxide (PPO), polyphenylene sulfide (PPS), styrene maleic anhydride copolymer (SMA) or styrene acrylonitrile copolymer (SAN).

[0006] The polymer alloy material of the present invention is based on polyolefin and specifically selects engineering plastics with high heat resistance and high modulus performance. Since polyolefin is a non-polar polymer and the selected engineering plastic is a polar polymer, the fluidity of the two is different, and the two can form a two-phase structure during the melt blending process; at the same time, the present invention needs to select a suitable compatibilizer for the corresponding engineering plastic to improve the compatibility between components and further improve the interface bonding effect of the two phases of the polymer. In addition, the added inorganic filler can improve the strength of the system and reduce the production cost. The auxiliary agent can effectively inhibit or reduce the thermal oxidation and photooxidation reaction speed of the engineering plastic macromolecules, and significantly improve the heat resistance and light resistance of the polymer material.

[0007] The components of the present invention work synergistically with each other to form a polymer alloy material with a "sea-sea" micro-dispersion feature and a dual-continuous phase structure with a tight interface. The polymer alloy material can simultaneously have excellent heat resistance, corrosion resistance, high flowability, low shrinkage, high modulus and other properties, making up for the shortcomings of the existing PP material of the flow battery plate frame plate.

[0008] In a preferred embodiment of the present invention, the polyolefin is homopolypropylene and / or its derivatives.

[0009] In some optional embodiments, the homopolypropylene derivative may be selected from chlorinated homopolypropylene and maleic anhydride grafted homopolypropylene.

[0010] In a preferred embodiment of the present invention, the compatibilizer is selected from one or more of maleic anhydride grafted polypropylene copolymer (PP-g-MAH), maleic anhydride grafted polyolefin elastomer copolymer (POE-g-MAH), maleic anhydride grafted styrene-ethylene / butylene-styrene block copolymer (MAH-SEBS) or maleic anhydride grafted polyethylene copolymer (PP-g-PE), polypropylene grafted butyl methacrylate copolymer (PP-g-BMA), polypropylene grafted polystyrene copolymer (PP-g-PS), hydrogenated styrene-butadiene block copolymer (SEBS), styrene-butadiene-styrene block copolymer (SBS) or ethylene-acrylic acid copolymer (EAA).

[0011] In a preferred embodiment of the present invention, the inorganic filler is selected from one or more of talc, wollastonite, silicon dioxide, quartz powder, glass powder, glass microbeads, glass fiber, magnesium hydroxide, diatomaceous earth or kaolin.

[0012] Adding inorganic fillers is important for polyolefin polymer materials. On the one hand, it can effectively increase the modulus of the material, and on the other hand, it can significantly reduce the molding shrinkage of the material. In actual production, taking PP as an example, if no inorganic filler is added when preparing the polymer alloy sample, the molding shrinkage of the sample will be above 1%. For the preparation of large-sized injection molded products, the high molding shrinkage will affect the surface morphology of the product, causing the originally flat product to shrink into a curved surface. At the same time, the selected inorganic filler can improve the acid resistance of polyolefin polymer materials.

[0013] In a preferred embodiment of the present invention, the polymer alloy material, by weight percentage, consists of 74% homopolypropylene, 10% polyphenylene ether, 3% ethylene-acrylic acid copolymer, 12% glass fiber, 0.5% antioxidant and 0.5% light stabilizer;

[0014] Or, the polymer alloy material, by weight percentage, consists of 25% homopolymer polyolefin, 20% polyphenylene ether, 4% maleic anhydride grafted polypropylene copolymer, 50% quartz powder, 0.5% antioxidant and 0.5% light stabilizer.

[0015] In some preferred embodiments, the auxiliary agent is selected from one or more of an antioxidant, a light stabilizer or a nucleating agent.

[0016] In some preferred embodiments, the antioxidant is selected from fully hindered phenol antioxidants and / or phosphite antioxidants; the light stabilizer is selected from one or more of benzophenone light stabilizers, benzotriazole light stabilizers or hindered amine light stabilizers; the nucleating agent is selected from dibenzhydryl sorbitol nucleating agents and / or substituted aromatic phosphate nucleating agents.

[0017] In some optional embodiments, the fully hindered phenol antioxidant is selected from antioxidant 1010, antioxidant 225, and 2,6-di-tert-butyl-p-cresol; the phosphite antioxidant is selected from trisnonylphenyl phosphite antioxidant TNP; the benzophenone light stabilizer is selected from UV-531 light stabilizer, the benzotriazole light stabilizer is selected from UV-327 light stabilizer, and the hindered amine light stabilizer is selected from LS-944 light stabilizer. In one aspect of the present invention, a method for preparing a polymer alloy material is provided, comprising the following steps:

[0018] Step S1, firstly melting a formulated amount of engineering plastic, and then preliminarily mixing a formulated amount of polyolefin, a compatibilizer and the molten engineering plastic;

[0019] Step S2, then kneading the inorganic filler and the auxiliary agent in the formula amount with the raw material processed in step S2 to obtain the mixed material;

[0020] Step S3, finally melt-extrude and granulate the mixture in sequence to obtain the polymer alloy material.

[0021] The present invention first melt-treats engineering plastics to form a molten state so that it is fully formed, so as to be fully mixed with polyolefins. Since polyolefins are non-polar polymers, and the engineering plastics selected are polar polymers, there are differences in the fluidity of the two. Under the action of mechanical force, the engineering plastics and polyolefins in the molten state can form a uniformly mixed dual-continuous phase structure. In addition, in the system, compatibilizers and polyolefins are added to the internal mixer together, and the interfacial bonding effect of the two phases can be further improved. Finally, inorganic fillers and auxiliary agents are added to further improve the mechanical strength, heat resistance, light resistance and other properties of polymer materials. Therefore, the present invention can construct a two-phase structure with "sea-sea" micro-dispersion characteristics and close interfacial bonding by the above-mentioned melt blending process, and then obtain a polymer alloy material having excellent heat resistance, corrosion resistance, high flow, low shrinkage, high modulus and other characteristics at the same time.

[0022] In a specific embodiment of the present invention, the internal mixing is carried out in an internal mixer, and the setting temperature of the internal mixer is 100-280°C, for example, it can be selected from 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 245 Preferably, the internal mixer is set at a temperature of 180 to 260°C and a speed of 30 to 60 r / min, for example, 10 r / min, 15 r / min, 20 r / min, 25 r / min, 30 r / min, 35 r / min, 38 r / min, 40 r / min, 45 r / min, 48 r / min, 50 r / min, 55 r / min, 58 r / min, 60 r / min. Further preferably, the internal mixer is set at a temperature of 180 to 260°C and a speed of 30 to 60 r / min.

[0023] In a specific embodiment of the present invention, the melting time is 3 to 5 minutes, for example, it can be selected from 3 minutes, 3.5 minutes, 4 minutes, 4.5 minutes, and 5 minutes; the initial mixing time is 4 to 7 minutes, for example, it can be selected from 4 minutes, 4.5 minutes, 5 minutes, 5.5 minutes, 6 minutes, 6.5 minutes, and 7 minutes; the mixing time is 3 to 5 minutes, for example, it can be selected from 3 minutes, 3.5 minutes, 4 minutes, 4.5 minutes, and 5 minutes.

[0024] In a specific embodiment of the present invention, the temperature of the melt extrusion process of the mixed material is 150-280° C., for example, it can be selected from 150° C., 160° C., 170° C., 180° C., 185° C., 190° C., 195° C., 200° C., 205° C., 210° C., 215° C., 220° C., 225° C., 230° C., 235° C., 240° C., 245° C., 250° C., 255° C., 260° C., 270° C., and 280° C. Further preferably, the temperature of the melt extrusion process is 190-260° C.

[0025] In a specific embodiment of the present invention, the extrusion rate of the melt extrusion of the mixed material is 20 to 80 r / min, for example, it can be selected from 20 r / min, 25 r / min, 30 r / min, 35 r / min, 38 r / min, 40 r / min, 45 r / min, 48 r / min, 50 r / min, 55 r / min, 58 r / min, 60 r / min, 65 r / min, 68 r / min, 70 r / min, 75 r / min, 78 r / min, and 80 r / min.

[0026] In the preparation method of the polymer alloy material of the present invention, by controlling the specific proportion of raw materials, and further controlling the temperature and shear rate of the melting process and the extrusion rate of the extrusion process, the dual-continuous phase structure of the polymer alloy material is further improved, the interface bonding is tighter, and the polymer alloy material with better performance is obtained.

[0027] Another aspect of the present invention provides a flow battery plate frame, which is made of the aforementioned polymer alloy material.

[0028] Based on the above reasons, the polymer alloy material of the present invention is particularly suitable for preparing plates and frames for liquid flow batteries, and the plates and frames can be mass-produced by injection molding. The plate and frame processing process has high production efficiency, stable and reliable quality, and low cost. The injection-molded thin-walled and large-area plate and frame products can meet the application requirements of the liquid flow battery system after being assembled into a battery stack, thereby realizing low-cost and large-scale production of liquid flow batteries and promoting the application and promotion of liquid flow battery technology.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The present invention adopts polyolefin as a matrix, and adds a specific proportion of high modulus and high heat-resistant engineering plastics, improves the compatibility between polymers by adding a compatible compatibilizer, and is supplemented with appropriate additives and inorganic fillers, and forms a polymer alloy material with a "sea-sea" microscopic dispersion feature and a double continuous phase structure with tight interface bonding through a melt blending process, so that it has the characteristics of high flow, high modulus, high heat resistance, strong acid resistance, low shrinkage rate, etc. The polymer alloy material of the present invention is particularly suitable for preparing the plate frame of the liquid flow battery, and the plate frame can be mass-produced by injection molding. The plate frame processing process has high production efficiency, stable and reliable quality, and low cost. The injection-molded thin-walled large-area plate frame products can meet the application requirements of the liquid flow battery system after being assembled into a battery stack, thereby realizing low-cost and large-scale production of liquid flow batteries and promoting the application and promotion of liquid flow battery technology. DETAILED DESCRIPTION

[0031] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0032] Example 1

[0033] A polymer alloy material, calculated by weight percentage, consists of 69% homopolypropylene, 19% styrene methyl methacrylate copolymer MS (model: Chimei PM-600), 1% maleic anhydride grafted polypropylene copolymer PP-g-MAH (model: Energy Light GPM200A), 10% quartz powder (3000 mesh), 0.5% antioxidant (Lianlong, B225) and 0.5% light stabilizer (Lianlong, UV-944DF).

[0034] The polymer alloy material was prepared by the following method: first, MS was added to an internal mixer (temperature of 180°C), melted at a speed of 10 r / min for 3 minutes, and then PP-g-MAH and PPH-T03 were added to the internal mixer, and initially mixed at a speed of 10 r / min for 4 minutes; then quartz powder, antioxidant, and light stabilizer were added to the internal mixer for internal mixing, and internal mixing was carried out at a speed of 50 r / min for 3 minutes to obtain a mixture. Finally, the mixture was melt-extruded (extrusion rate of 50 r / min, melt extrusion temperature of 190°C) and granulated to obtain a polymer alloy material.

[0035] Example 2

[0036] A polymer alloy material, calculated by weight percentage, consists of 74% homopolypropylene, 10% polyphenylene ether PPO (model: Xinbao XB040), 3% ethylene-acrylic acid copolymer EAA (model: SK 1040), 12% flat micro-powdered glass fiber (Chongqing International), 0.5% antioxidant (Lianlong, B225) and 0.5% light stabilizer (Lianlong, UV-944DF).

[0037] The polymer alloy material is prepared by the following method: first, PPO is added to an internal mixer (temperature is 280°C), melted at a speed of 10r / min for 3 minutes, then EAA and homopolypropylene are added to the internal mixer, and initially mixed at a speed of 10r / min for 4 minutes; then glass fiber, antioxidant, and light stabilizer are added to the internal mixer for internal mixing, and internal mixing is carried out at a speed of 50r / min for 3 minutes to obtain a mixture, and finally the mixture is melt-extruded (extrusion rate is 60r / min, melt extrusion temperature is 255°C) and granulated to obtain a polymer alloy material.

[0038] Example 3

[0039] A polymer alloy material, calculated by weight percentage, consists of 79% homopolypropylene, 10% styrene acrylonitrile copolymer SAN (model LG Yongxing 80HF), 5% maleic anhydride grafted styrene-ethylene / butylene-styrene block copolymer MAH-SEBS (model Kraton FG1901), 5% talc (4000 mesh), 0.5% antioxidant (Lianlong, B225) and 0.5% light stabilizer (Lianlong, UV-944DF).

[0040] The polymer alloy material was prepared by the following method: first, SAN was added to an internal mixer (temperature of 210°C) and melted at a speed of 10 r / min for 3 minutes, and then MAH-SEBS and homopolypropylene were added to the internal mixer and initially mixed at a speed of 10 r / min for 4 minutes; then talcum powder, antioxidant, and light stabilizer were added to the internal mixer for internal mixing, and the mixture was obtained by internal mixing at a speed of 50 r / min for 3 minutes. Finally, the mixture was melt-extruded and granulated (extrusion rate of 70 r / min, melt extrusion temperature of 205°C) to obtain a polymer alloy material.

[0041] Example 4

[0042] A polymer alloy material, which is composed, by weight percentage, of 73% homopolypropylene, 5% styrene acrylonitrile copolymer SAN (Chimei PN-117C), 8% polycarbonate PC, 1% MAH-SBS (Kumho KTR403), 8.5% talc (Imerys T88), 4% antioxidant (Lianlong, B225) and 0.5% light stabilizer (Lianlong, UV-944DF).

[0043] The polymer alloy material was prepared by the following method: first, SAN and PC were added to an internal mixer (temperature of 210°C), melted at a speed of 10 r / min for 3 minutes, and then MAH-SBS and homopolypropylene were added to the internal mixer and initially mixed at a speed of 10 r / min for 4 minutes; then talcum powder, antioxidant, and light stabilizer were added to the internal mixer for internal mixing, and internal mixing was carried out at a speed of 50 r / min for 3 minutes to obtain a mixture, and finally the mixture was melt-extruded and granulated (extrusion rate of 45 r / min, melt extrusion temperature of 210°C) to obtain a polymer alloy material.

[0044] Example 5

[0045] A polymer alloy material, which is composed, by weight percentage, of 44.5% homopolypropylene, 5% styrene acrylonitrile copolymer SAN (Chimei PN-117C), 8% PC, 5% MAH-SBS (Kumho KTR403), 35% needle-shaped wollastonite (Fangjiashan WF05), 2% antioxidant (Lianlong, B225) and 0.5% light stabilizer (Lianlong, UV-944DF).

[0046] The polymer alloy material was prepared by the following method: first, SAN and PC were added to an internal mixer (temperature of 260°C), melted at a speed of 10 r / min for 3 minutes, and then MAH-SBS and homopolypropylene were added to the internal mixer and initially mixed at a speed of 10 r / min for 4 minutes; then, needle-shaped wollastonite, antioxidant, and light stabilizer were added to the internal mixer for internal mixing, and the mixture was obtained by internal mixing at a speed of 50 r / min for 3 minutes. Finally, the mixture was melt-extruded and granulated (extrusion rate of 55 r / min, melt extrusion temperature of 255°C) to obtain a polymer alloy material.

[0047] Example 6

[0048] A polymer alloy material, which is different from Example 1 in that homopolymer polyolefin is 25%, engineering plastic polyphenylene ether PPO is 20%, compatibilizer is 4%, inorganic filler is 50%, and auxiliary agent is 1%. Its preparation method is the same as Example 1.

[0049] Example 7

[0050] A polymer alloy material, which is different from Example 2 in that homopolymer polyolefin is 50%, styrene methyl methacrylate copolymer MS is 15%, compatibilizer is 3%, inorganic filler is 30%, and auxiliary agent is 2%. Its preparation method is the same as Example 2.

[0051] Comparative Example 1

[0052] A polymer blend material consists of 69% homopolypropylene, 30% quartz powder (3000 mesh), 0.5% antioxidant (Rianlon, B225) and 0.5% light stabilizer (Rianlon, UV-944DF) according to weight percentage.

[0053] The polymer alloy material was prepared by the following method: homopolymerized polypropylene, antioxidant, light stabilizer and talcum powder were added into an internal mixer (temperature was 210° C.), and melted at a rotation speed of 50 r / min for 10 min to obtain a polymer blend material.

[0054] Performance Testing

[0055] The polymer alloy material of the above embodiment and the polymer blend material of the comparative example were tested for melt index, heat deformation temperature, impact strength, flexural modulus, acid resistance, and molding shrinkage. The test data are shown in Table 1.

[0056] The melt index is measured with reference to GB / T 3682.1-2018; the heat deformation temperature of the sample is carried out in accordance with the relevant requirements of GB / T1633-2000 (1.8MPa weight); the impact strength is tested according to the method specified in GB / T1043.1-2008; the flexural modulus is tested according to the method specified in GB / T14694, and the molding shrinkage is tested according to GB / T14233.2-2005 "Dimensional Tolerances of Injection Molded Plastic Products".

[0057] The acid resistance test method is: heat the sample in 30% concentrated hydrochloric acid at 70°C for 24 hours. The concentrated hydrochloric acid before treatment does not contain metal cations, so the metal ion content in the concentrated hydrochloric acid after treatment can reflect the tolerance of inorganic powder to 30% concentrated hydrochloric acid. Dilute the clear liquid after the reaction and use ion chromatography to detect the metal ion concentration.

[0058] Table 1. Material performance test table of comparative example 1 and each embodiment

[0059]

[0060] As can be seen from Table 1, the strength, bending modulus, shrinkage and heat resistance of the materials in the embodiments of the present invention are significantly improved compared with Comparative Example 1. Since the amount of ion precipitation is closely related to the variety and addition of inorganic fillers in the material, the inorganic fillers of each embodiment are different, resulting in a large difference in the amount of ion precipitation, but the ion output of each embodiment is less than 20ppm, and all show better acid resistance. The comprehensive performance of this embodiment is excellent in Comparative Example 1. This is because the engineering plastics specifically selected by the present invention are added to the polymer materials in the embodiments of the present invention, which are polar polymer materials, and have a large difference in fluidity with polyolefins, forming a polymer alloy material with a double continuous phase structure with "sea-sea" microscopic dispersion characteristics and close interface bonding, which greatly improves the heat resistance, corrosion resistance, flow, shrinkage, and bending modulus of the material. From the perspective of comprehensive performance, the performance data of Examples 2 and 6 of the present invention are the best.

[0061] The amount of ion precipitation in the acid resistance test is a key factor in evaluating the performance of the sample. Therefore, when designing a reasonable sample plan, the type and addition amount of the inorganic filler should be comprehensively considered. According to the experimental research of the inventor, the addition amount of 5-50% is a more appropriate range.

[0062] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A polymer alloy material, characterized in that: The polymer alloy material comprises the following components in 100% by weight: 25-80% of polyolefin, 10-20% of engineering plastic, 1-5% of compatibilizer, 5-50% of inorganic filler and 0.1-5% of additive; wherein the engineering plastic is selected from one or more of styrene methyl methacrylate copolymer, styrene-butadiene methyl methacrylate copolymer, polycarbonate, polyphenylene ether, polyphenylene sulfide, styrene-maleic anhydride copolymer or styrene-acrylonitrile copolymer.

2. The polymer alloy material according to claim 1, characterized in that: The polyolefin is homopolypropylene and / or its derivatives.

3. The polymer alloy material according to claim 1, characterized in that: The compatibilizer is selected from one or more of maleic anhydride grafted polypropylene copolymer, maleic anhydride grafted polyolefin elastomer copolymer, maleic anhydride grafted styrene-ethylene / butylene-styrene block copolymer, maleic anhydride grafted polyethylene copolymer, polypropylene grafted butyl methacrylate copolymer, polypropylene grafted polystyrene copolymer, hydrogenated styrene-butadiene block copolymer, styrene-butadiene-styrene block copolymer or ethylene-acrylic acid copolymer.

4. The polymer alloy material according to claim 1, characterized in that: The inorganic filler is selected from one or more of talc, wollastonite, silicon dioxide, quartz powder, glass powder, glass microbeads, glass fiber, magnesium hydroxide, diatomaceous earth or kaolin.

5. The polymer alloy material according to any one of claims 1 to 4, characterized in that: The polymer alloy material is composed of 74% homopolypropylene, 10% polyphenylene ether, 3% ethylene-acrylic acid copolymer, 12% glass fiber, 0.5% antioxidant and 0.5% light stabilizer according to weight percentage; Or, the polymer alloy material, by weight percentage, consists of 25% homopolymer polyolefin, 20% polyphenylene ether, 4% maleic anhydride grafted polypropylene copolymer, 50% quartz powder, 0.5% antioxidant and 0.5% light stabilizer.

6. The method for preparing a polymer alloy material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step S1, firstly melting a formulated amount of engineering plastic, and then preliminarily mixing a formulated amount of polyolefin, a compatibilizer and the molten engineering plastic; Step S2, then kneading the inorganic filler and the auxiliary agent in the formula amount with the raw material processed in step S2 to obtain a mixed material; Step S3, finally melt-extrude and granulate the mixture in sequence to obtain the polymer alloy material.

7. The method for preparing a polymer alloy material according to claim 6, characterized in that: The internal mixing is carried out in an internal mixer, and the setting temperature of the internal mixer is 100-280° C. and the rotation speed is 10-60 r / min.

8. The method for preparing a polymer alloy material according to claim 7, characterized in that: The melting time is 3 to 5 minutes; the initial mixing time is 4 to 7 minutes; and the banburying time is 3 to 5 minutes.

9. The method for preparing a polymer alloy material according to claim 6, characterized in that: The temperature of the melt extrusion process of the mixed material is 150-280° C., and the extrusion rate is 20-80 r / min.

10. A liquid flow battery plate frame, characterized in that: The polymer alloy material as claimed in claim 1 is used for preparation.

Citation Information

Patent Citations

  • High-temperature-resistant high-impact-resistant polyphenylether / polypropylene alloy material and preparation method thereof

    CN103450561A

  • Polyphenyl ether / polypropylene copolymer blended alloy material and preparation method thereof

    CN104277446A

  • Glass fiber modified PP / AS alloy material

    CN106519435A

  • PP / PPO (polypropylene / propylene oxide) alloy and preparation method thereof

    CN106928542A

  • Modified polyphenyl ether and polypropylene resin alloy material and preparation method thereof

    CN108676345A

Cited By

  • Preparation method of plate frame material for direct stack welding of flow batteries, plate frame and plate frame welding process

    CN120518954A

  • A method of preparing a plate and frame material for direct stack welding of a flow battery, a plate and frame, and a plate and frame welding process

    CN120518954B